2007
DOI: 10.1111/j.1442-9993.2007.01681.x
|View full text |Cite
|
Sign up to set email alerts
|

Ground‐dwelling beetle assemblages in the northern Cape Floristic Region: Patterns, correlates and implications

Abstract: Recent studies have both shown and predicted that global climate change will have a substantial influence on biodiversity.This is true especially of a global biodiversity hotspot, the Cape Floristic Region. Although the effects of predicted changes have been widely assessed for plants, little is known about how insect diversity in the region might be affected. In particular, patterns in and the correlates of diversity in the region are poorly understood, and therefore the likely affects of a changing abiotic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
1
4

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 93 publications
(112 reference statements)
0
32
1
4
Order By: Relevance
“…An example of this are N. rotundipennis, Emmallodera obesa costata Kulzer, Nyctopetus argentinus Freude and Scotobius alaticollis Kulzer that have become common insects in scrublands and open and dry forests (Mazía et al, 2006;Sackmann et al, 2008). A similar pattern has been described for the Cape floristic region, where the eastward decline in species richness of tenebrionid assemblages reflects movement away from the southern end of the south-west African centre of tenebrionid endemism and diversity (Botes et al, 2007).…”
Section: Differences In Species Richness and Composition Between The mentioning
confidence: 58%
See 2 more Smart Citations
“…An example of this are N. rotundipennis, Emmallodera obesa costata Kulzer, Nyctopetus argentinus Freude and Scotobius alaticollis Kulzer that have become common insects in scrublands and open and dry forests (Mazía et al, 2006;Sackmann et al, 2008). A similar pattern has been described for the Cape floristic region, where the eastward decline in species richness of tenebrionid assemblages reflects movement away from the southern end of the south-west African centre of tenebrionid endemism and diversity (Botes et al, 2007).…”
Section: Differences In Species Richness and Composition Between The mentioning
confidence: 58%
“…These adaptations are mostly influenced by temperature; however other factors such as vegetation type and soil topography may also affect their distribution and abundance (e.g. Ayal and Merkl, 1994;Botes et al, 2007;Krasnov and Ayal, 1995). Tenebrionid assemblages usually show spatial and temporal change in relation to variation in the environmental conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, two types of species richness patterns are frequently observed with increasing altitude: a monotonicdecreased due to resource limitation and thermal constraints (Fiedler and Beck, 2008) or a hump-shaped (Colwell and Lees, 2000) pattern due to the combined effects of many environmental variables and associated processes promoting the co-occurrence of many species (Lomolino, 2001). Although not assessed in a statistical framework, ground beetle assemblages have been reported to show a monotonic-decreased in species richness with increasing altitude (Greenslade, 1968;Meyer and Thaler, 1995;Butterfield, 1996;Gobbi et al, 2007), but some studies reported a hump-shaped pattern for altitudes from 1000 to 2600 m (Suttiprapan et al, 2006) or a hump-shaped pattern with an increase at the summit area from 0 to 1900 m (Botes et al, 2007). However, these previous studies provided limited information; only the dominant vegetation or temperatures at the altitudes investigated were reported.…”
Section: Introductionmentioning
confidence: 95%
“…they show habitat specificity and fidelity (Thiele, 1977;Lövei and Sunderland, 1996;Rainio and Niemelä, 2003;Pearce and Venier, 2006;Botes et al, 2007). These ecological characteristics of ground beetles make them ideal organisms for study to assess biodiversity and habitat characteristics along environmental gradients.…”
Section: Introductionmentioning
confidence: 97%